2003
DOI: 10.4188/jte.49.14
|View full text |Cite
|
Sign up to set email alerts
|

Welding Flow of Low Density Polyethylene Melt

Abstract: Weld-lines degrade the mechanical and optical properties of products. This is because the polymer molecules near the weld-line highly orient owing to the elongational flow and the molecular orientation is fixed by solidification of the polymer melts before it returns to a random condition. Birefringence experiments were, therefore, carried out for welding flows of a low density polyethylene (LDPE) past a spider supporting a mandrel. The die used in the present study has a glass window to observe the birefringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The distribution of N1 ( Fig. 8) allows to conclude that when the spider leg is closer to the die exit the flow front interface is subjected to high average N1 values, which is known to difficult the molecular entanglement between different flow fronts [14][15][16][17]. This is in accordance with the experimental results obtained (Fig.…”
Section: Figuresupporting
confidence: 87%
See 4 more Smart Citations
“…The distribution of N1 ( Fig. 8) allows to conclude that when the spider leg is closer to the die exit the flow front interface is subjected to high average N1 values, which is known to difficult the molecular entanglement between different flow fronts [14][15][16][17]. This is in accordance with the experimental results obtained (Fig.…”
Section: Figuresupporting
confidence: 87%
“…1a, the relative fatigue life was reduced cca 90%. Later, Mitsuhashi et al [15][16][17] presented a remarkable numerical study, extending the work developed by Huang and Prentice to viscoelastic fluids. They showed that by changing only the attack angle of the upstream spider leg region (see Fig.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations